2021
DOI: 10.3389/fneur.2021.710783
|View full text |Cite
|
Sign up to set email alerts
|

Goal-Concordant Care After Severe Acute Brain Injury

Abstract: Background: Patients with severe acute brain injury (SABI) lack decision-making capacity, calling on families and clinicians to make goal-concordant decisions, aligning treatment with patient's presumed goals-of-care. Using the family perspective, this study aimed to (1) compare patient's goals-of-care with the care they were receiving in the acute setting, (2) identify patient and family characteristics associated with goal-concordant care, and (3) assess goals-of-care 6 months after SABI.Methods: Our cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Although no score will replace the clinician’s expertise and clinical assessment for a given patient, predictive scores could help navigate this uncertainty. Clinicians’ reluctance to use scores has already been described [ 12 , 36 , 37 ]; nevertheless, many prognostic scores have been shown to be more accurate than clinical judgement, even for experienced clinicians [ 9 ]. Clinicians’ estimate of terminally ill patients’ survival is also known to be inaccurate and most often overestimated, which impacts LST decisions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no score will replace the clinician’s expertise and clinical assessment for a given patient, predictive scores could help navigate this uncertainty. Clinicians’ reluctance to use scores has already been described [ 12 , 36 , 37 ]; nevertheless, many prognostic scores have been shown to be more accurate than clinical judgement, even for experienced clinicians [ 9 ]. Clinicians’ estimate of terminally ill patients’ survival is also known to be inaccurate and most often overestimated, which impacts LST decisions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…When patients lack decision-making capacity, their surrogate decision makers are called upon to make decisions on their behalves. While most patients prefer their family members to act as surrogate decision makers, [ 9 ], family members often feel unprepared for making LST decisions in acute situations given the uncertainty and the moral burden of such decisions [ 10 , 11 , 12 ]. Several strategies have been suggested to better support families facing LST decisions, but the effect of these interventions on psychological distress has been limited [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 However, recent studies demonstrated that over 70% of patients with acute brain injury and family members' who perceived comfortoriented care as the prioritized therapeutic goal received goal-discordant care. 1 The need for rapid decision-making complicates discussions regarding acute therapies for neurologic emergencies and MOLST reversal. For example, thrombectomy for ischemic stroke requires rapid treatment decisions and has diminishing returns on outcomes with passing time.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, recent studies demonstrated that over 70% of patients with acute brain injury and family members’ who perceived comfort-oriented care as the prioritized therapeutic goal received goal-discordant care. 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation